Dimensi-Dimensi Hukum Pidana Islam Dalam Sanksi Tindak Pidana Begal - Wahyuni, Siska; Gunawan, Hendra (Jurnal El-Thawalib, 2023)
The problem in this research are the dimensions of islamic criminal law in the criminal act of robbery. The type of research  used is library research using a normatif yuridis approach, namely by using statutory approach. The main data source is the primary data source, namely in article 365 of the criminal code. And secondary data sources are taken from books, legal journal articles, and related documents. Data collection technique or legal materials by identifying data introduction and editing (acurate data checking), This research data analysis technique is by interpreting the data according to the purpose, design and nature of the research. The result of the research obtained in islamic law the sanctions  for legal perpetrators areexile, cross cut hands and peet, santenced to death and exile while in the ciminal code the punishment for legal is only imprisonment and death penaltu, ift the acct does not kill the victim  then the sentence is 9-12 years prison, and the sentence is increased to 15 years if someone dies, that the dimension of islamic criminal law in sanctions for criminal acts of robbery is hudud finger. Therefore, the sanctions for perpetrators off robbery in article 365 of the criminal code are very light when compared to the sanctions for perpetrators of robberies in islmic law.